1026Female-Headed Households: Gender and Health Inequalities. (2nd September 2021) - Saad, Ghada; DeJong, Jocelyn; Ghattas, Hala; Barros, Aluisio; Wendt, Andrea; Hellwig, Franciele
Abstract: Background: Gender norms greatly affect who is the main breadwinner and decision maker in a household. Commonly, in the Middle East and North Africa (MENA) region, males are the household heads and it is believed that female-headed households (FHH) are more disadvantaged compared to male-headed households (MHH). Our analysis identifies a household typology and illustrates differences in social inequalities and child health outcomes by headship gender. Methods: We used DHS/MICS surveys in MENA to identify three types: MHH, and FHH with/without males. We analyzed differentials in birth registration, care-seeking for health treatment, obesity, stunting and full vaccination, wealth quintiles, head's education and residence. Results: Among nine countries with surveys since 2010, the average prevalence of FHH was 12%. Female heads were generally over 50 years and had no or primary education. FHH are generally poorer, especially FHH with no males. In Algeria, Iraq, Morocco and Yemen, the proportions of FHH with males present were larger in the richer quintiles, compared to other household types. Disparities in child indicators varied by country, and were not evident for birth registration, vaccination and obesity. Care-seeking was higher among FHH. Stunting was higher among FHH without males. Conclusions: Disparities in child health indicators are not evident across the household types. However, there were differences in household wealth and head's education by household type. Female headship is an important dimension of inequality, but there are differences within that category. Key messages: Despite being socially disadvantaged, children in FHH received similar healthcare compared to children in MHH.